Frequency of Thyrotoxicosis in Fifty Patients previously treated for anxiety neurosis - Khan, Sheema; Ahmad, Sarfaraz (Journal of Postgraduate Medical Institute, 2011)
To determine the frequency of thyrotoxicosis in 50 consecutive patients presenting with anxiety as chief complaint. Who have been previously treated with anxiolytics and anti-deparessants. This prospective analystical study was conducted in the medical OPD of HMC, peshawar from january 2004 to June 2004. patietns with symptoms of palpitations. Weating. tremors, anorexia and weight loss and those experiencing periods of intense fear and who were previously treated with anxioloytics were included in the study. All those patients who had diagnosed thyroid disease, were being treated for thyroid disease or had undergone thyroid surgery or radioablation of thyroid gland were excluded. In addition patients who had anxiety with concommitant medical disease, as tuberculosis. hepatitis diabetes or hypertension etc and those on anti arrythmic drug after a detail history and clinical examination, thyroid function tests. ECG was performed in all patients. Thyrotoxicosis is a common cause of anxiety neurosis in patients treated with anxiolytics. it should be excluded before a diagnosis of anxielty disorder is made.